Study of Common Construction Practices and Structural Defects in RC Buildings in Darchula District Far-Western Nepal - Bohara, Birendra Kumar (Far Western Review, 2023)
This paper presents the common construction and structural deficiencies noticed in Mahakali municipality Darchula. The RC building constructions are common in the Darchula district. The main objective of this study is to find existing structural and construction mistakes in RC buildings. Field observations, interviews with engineers, technical people, local house owners, photographs, reviews of works of literature, bye-laws, buildings code, etc. are taken to fulfill the objective ofthe study. This paper examines the cause and effects of faulty construction practices and structural defects by using both analytical and numerical methods. Structural defects are present in the RC buildings due to improper construction methods, poor use of bye[1]laws, poor workmanship; do not consult with professionals, corruption, lack of training, etc. The results show that these structural defects and faulty constructions practice may lead to serious failures of structures during strong earthquakes. This study provides relevant information on the building’s collapse in a recent earthquake (Gorkha 2015) and the major cause of failure of RC buildings to compare the defects present in existing RC buildings in the Darchula district. The results concluded that almost 48% of buildings have column sizes less than 300mmx300mm, 24% of buildings have poor beam-column joints and 11% of buildings are soft storey and irregular building shapes. The numerical results pointed out that non-engineered buildings show poor seismic performance, poor seismic capacity and failure mechanism. The study strongly recommended that to prevent future hazards, the construction of buildings should follow the building’s laws and codes and also should be ensured by the municipality and other government bodies also provides sufficient training and knowledge in the local level. To improve the existing structures, it is important to increase the strength capacity and ductility of the joint by providing a suitable retrofitting process or maintenance process.